Accessing the deuteron source with pion-deuteron femtoscopy in Pb-Pb collisions at √sNN=5.02 TeV - Acharya, S.; Agarwal, A.; Rinella, G. Aglieri; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; Akishina, V.; et al. (AMER PHYSICAL SOC, 2025)
Femtoscopy of nonidentical particle pairs has been instrumental for precision measurements of both two-particle sources and the final-state interactions in high-energy elementary and heavy-ion collisions. The majority of measurements assessing the source properties are based on identical particle pairs, providing direct access to the characteristics of the single-particle source. The work in this paper demonstrates, via femtoscopy measurements of charged pion-deuteron pairs in Pb-Pb collisions at root s(NN) = 5.02 TeV, the feasibility of accessing the characteristics of the single-particle femtoscopic source by using particle pairs with large mass differences such as pions and deuterons. The first experimental results of the measurement of deuteron source sizes in ultrarelativistic heavy-ion collisions are presented. The results show good agreement with the trend derived from other charged hadrons such as pions, kaons, and protons as a function of transverse mass, indicating similar source properties.
Keywords: LIGHT-NUCLEI; MULTIPLE PRODUCTION; SCATTERING LENGTHS; INTERFERENCE; ENERGY; QCD; Physics